Recurrent Ameloblastoma: A Surgical Challenge - Chithra Aramanadka; Abhay Taranath Kamath; Adarsh Kudva (Case Reports in Dentistry)
Ameloblastoma is locally aggressive benign odontogenic tumour with increased risk of recurrence rate. The choice of treatment depends on the histologic subtype. Radical therapy is the recommended modality for solid ameloblastomas. The possibilities of recurrence even after enbloc resection are still high. The author presents two case reports of recurrent ameloblastomas postradical resection. First case describes the recurrence of ameloblastoma in the bone graft which was used for reconstruction, and the second case depicts recurrence in the infratemporal fossa. Intraoperative radiography of the frozen section of the soft tissue margin plays an important role in the holistic management of these lesions.